Oxidative stress mechanisms as potential therapeutic targets in chronic kidney disease - Dobrek, Łukasz (Medical Studies/Studia Medyczne, 2022)
Chronic kidney disease (CKD) is a gradual loss of kidney function over time, leading to the development of kidney failure. CKD is a consequence of common civilization diseases, such as arterial hypertension and diabetes, as well as primary kidney and urinary tract diseases of various aetiologies. The pathogenesis of CKD is complex, and the ongoing inflammation and increased oxidative stress (OS) in kidney tissues also play a significant role in the CKD pathophysiological description. Hence, attempts are being made to pharmacologically modify these important pathophysiological pathways. This article presents a brief overview of the aetiopathogenesis of OS in the course of CKD and briefly lists the research on the novel compounds with expected OS-alleviating activity in CKD based on their interference with selected pathophysiological pathways (xanthine oxidase inhibitors, nicotinamide adenine dinucleotide phosphate oxidase inhibitors, protein kinase C inhibitors, transforming growth factor  inhibitors, or activators of nuclear factor erythroid 2-related factor 2).